The role of organisational experience to support job readiness: A phenomenological approach of fresh graduates - Handoko, Pryo (Technium Social Sciences Journal, 2021)
We have known that organisation provides positive values that will make students get new experiences that will not be possible from the lecture hall alone. Organisational activities will provide space for students to be creative and active more widely. Students will interact a lot with other people from different backgrounds. This study aims at answering the questions on what experiences gained by fresh graduates by joining actively in student organisation, what factors cause students not interested in joining organisations, and what solutions must be taken so that the quality of student organisations can be maintained. In this research, a phenomenological approach is employed and semi structured interviews were conducted to a total of 40 participants, consist of 15 fresh graduates who were active in organisations, 15 fresh graduates who were not active in organisations and 10 HRD managers. The research proved that fresh graduates who were active in student organisations have better skills in communication, broader insights that are able to hone creativity and critical thinking, have the ability to work together, higher responsibility and maturity, and are able to adapt to the new environment, so that they are more prepared to enter the world of work.